Product Factors Affecting Milk Choices among Chinese Older Adults - Chen A; Moradi S; Hort J (MDPI (Basel, Switzerland), 2024)
In China, milk is promoted both as an optimal food and gift for older adults. To understand the product factors affecting older Chinese adult milk choices, choice simulations and surveys were conducted in Beijing, Shanghai, Guangzhou, Chengdu, and Shenyang, China. Participants (n = 1000, aged 45-55 years old and 65-75 years old) were asked to choose one milk product out of eight alternatives for self-consumption and gifting, respectively, and to indicate product factors under their considerations. Results showed that, for self-consumption, the top four most popular milk products (two with domestic brands and two with international brands) were chosen by 84.9% of the participants. Females and younger participants were more open to international brands than their counterparts. Popular milk products differed across cities, potentially due to brand familiarity. Brand (85.9%), on-the-pack, nutrition-related well-being messaging (72.9%), price (63.1%), shelf-life (63.0%), and production date (57.6%) were the most frequently reported product factors considered when choosing milk. More males considered price than females (66.9% vs. 60.0%, p = 0.02). Female and older participants showed greater concern for certain detailed product factors, such as production date and shelf-life, than their counterparts. Variation across cities was limited, with participants in Chengdu and Shenyang showing less concern for certain product factors such as on-the-pack, certificate-related well-being messaging. When milk products were chosen as a gift, although overall milk choice ranking remained similar, package style received increased attention (32.0% vs. 40.8%, p < 0.01), whilst all other product factors, especially price (63.1% vs. 49.5%, p < 0.01), were considered by significantly fewer participants. These findings provide valuable marketing insights, helping to understand consumer preferences and considerations in the process of milk purchase decision-making.
Keywords: Chinese milk consumption; choice simulation; gifting behaviour; milk targeting older adults